THE OCCURRENCE OF PALAEOZOIC CONGLOMERATIC ROCKS IN EAST JOHOR, PENINSULAR MALAYSIA - Sugeng Sapto Surjono; Mohd Shafeea Leman; Kamal Roslan Mohamed; Che Aziz Ali (Geological Engineering Department Universitas Gadjah Mada, 2015)
Conglomeratic rocks in East Johor are found in the separately three formations that are the Murau, Tanjung Leman and Linggiu Formations. The Murau Formation is characterized by cobble to boulder grained breccia with very angular to angular and disorganized clasts. It was deposited by fan-delta system in the sub-aerial to shallow marine environment. The Tanjung Leman Formation consists of pebble to cobble grained conglomerate with rounded to subrounded and organized clasts. It was deposited by braided river system in the sub-aerial environment. Both formations outcropped in eastern coastal of Johor. The rudaceous rocks of the Linggiu Formation consist of pebble to cobble-sized clasts with sub angular and disorganized texture. It present as subordinate rocks within sandstone dominant in the central part of East Johor and was deposited by debris flows in the shallow marine environment. All these rudaceous rocks were interpreted as Palaeozoic in age ranging from Late Carboniferous to Late Permian. Those rudaceous rocks indicated that since Late Carboniferous, palaeogeography of East Johor was a continent with subaerial to shallow marine depositional environment. Keywords: Conglomerate, Palaeozoic, East Johor, subaerial, shallow marine.